Direct fabrication of crystalline hydroxyapatite coating on zirconium by single-step plasma electrolytic oxidation process - Cengiz, Sezgin; Uzunoglu, Aytekin; Stanciu, Lia; Tarakçı, Mehmet; Gencer, Yücel (Elsevier Science Sa, 2016)
This is the first report on the growth of a crystalline hydroxyapatite (HA) coating on zirconium substrate using a facile plasma electrolytic oxidation (PEO) method. The crystalline HA layers were fabricated in a Ca(CH3COO)(2) x 5H(2)O, C3H7Na2O6P x 5H(2)O, and KOH containing electrolyte. The prepared coatings were characterized by X-ray diffractometry (XRD), scanning electron microscopy (SEM), contact angle goniometry (CAG) and energy dispersive spectroscopy (EDS). In addition, Fourier transform infrared spectroscopy (FTIR) was used to examine the molecular bond structure of the coating. The results revealed that the composition of the oxide layer formed on zirconium surface includes hydroxyapatite, calcium zirconium oxide, and monoclinic zirconia. The FUR and XRD results confirmed the formation of crystalline HA layers on the surface of Zr substrate. It was concluded that PEO of Zr substrate is a valid method to prepare crystalline HA coatings with a low contact angle value for biomedical applications due to its easy and fast nature. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Hydroxyapatite; Plasma electrolytic oxidation; Zirconium; Nano-structure; Hydrophilic coating